2021
DOI: 10.4102/phcfm.v13i1.2424
|View full text |Cite
|
Sign up to set email alerts
|

The perception and knowledge about episiotomy: A cross-sectional survey involving healthcare workers in a low- and middle-income country

Abstract: Background: Episiotomy was introduced into clinical practice without clear evidence of its benefits.The knowledge and understanding of episiotomy guidelines and practice by healthcare workers is substandard in our setting; hence, the injudicious use of this procedure have led to high rates.Aim: To assess the knowledge, perception and practice of episiotomy by healthcare workers.Setting: Research was conducted in a Pietermaritzburg complex, South AfricaMethods: A questionnaire-based survey was conducted amongst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Seijmonsbergen-Schermers et al 21 state that episiotomy may be necessary to prevent fetal suffering in cases of prematurity and that it may also be necessary in cases of prolonged labor to facilitate a faster delivery, which is consistent with the findings of Masuda et al 25 and other studies [22][23][24]26 . This practice reduces maternal effort and prevents fetal distress, thereby facilitating labor 27 .…”
Section: Factors Related To Childbirthsupporting
confidence: 63%
See 1 more Smart Citation
“…Seijmonsbergen-Schermers et al 21 state that episiotomy may be necessary to prevent fetal suffering in cases of prematurity and that it may also be necessary in cases of prolonged labor to facilitate a faster delivery, which is consistent with the findings of Masuda et al 25 and other studies [22][23][24]26 . This practice reduces maternal effort and prevents fetal distress, thereby facilitating labor 27 .…”
Section: Factors Related To Childbirthsupporting
confidence: 63%
“…This results in a lack of confidence during labor without instrumentation. Other authors 26,27 suggest that the recurrent practice of episiotomy may be due to a lack of theoretical and practical knowledge about the physiology of the perineum and the expulsive period of labor. The education of health professionals 23 and their experiences and training also influence the decision to perform this procedure.…”
Section: Factors Related To Healthcare Professionalsmentioning
confidence: 99%
“…The evidence showed that selective episiotomy with appropriate identification, diagnosis, and timing reduces the rate of practice and associated complications, 17 , 18 this is why World Health Organization (WHO) suggests a restrictive episiotomy policy other than the routine practice of episiotomy performed with care provider’s perception and attitude, misdiagnosis and without pertinent obstetric and maternal indication. 19 The extent of episiotomy practice was determined by the presence or absence of the protocol or policy for health care providers, work experience, and professions. 7 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…3,16 The evidence showed that selective episiotomy with appropriate identification, diagnosis, and timing reduces the rate of practice and associated complications, 17,18 this is why World Health Organization (WHO) suggests a restrictive episiotomy policy other than the routine practice of episiotomy performed with care provider's perception and attitude, misdiagnosis and without pertinent obstetric and maternal indication. 19 The extent of episiotomy practice was determined by the presence or absence of the protocol or policy for health care providers, work experience, and professions. 7,20 Ethiopian ministry of health is providing emergency obstetrics and new-borne care (BEmONC) training in partnership with non-governmental organizations for obstetrics care providers to advance their performances and reduce maternal mortality and morbidity, increase institutional delivery and improve women's satisfaction with the quality of care by avoiding unnecessary obstetrics interventions or mistreatment.…”
Section: Introductionmentioning
confidence: 99%
“…The experiences of those who had episiotomies align with O'Kelly et al (2017), emphasizing the need for better communication during consent, timely suturing, and post-procedure support [ 23 ]. Complications reported by Maphanga et al (2021) emphasize the importance of addressing and lessening complications through tailored care plans [ 24 ].…”
Section: Discussionmentioning
confidence: 99%